Time and temperature stability of Tritrichomonas foetus in phosphate-buffered saline as evaluated by a reverse transcription real-time PCR assay and field analysis - Loy, Duan S.; Spuri Gomes, Renata; Dutta, Enakshy; Brodersen, Bruce W.; Loy, John Dustin (Frontiers in Veterinary Science, 2023)
Tritrichomonas foetus (TF) is a significant reproductive pathogen of cattle and sample collection, handling, transport and testing are significant hurdles to surveillance programs. Recent methods have been developed that allow for direct detection of TF using a reverse transcription real time PCR (Direct RT-qPCR) approach. To evaluate these methods, a comparative analysis was conducted to assess the technical performance of this assay with a commercially available real-time PCR assay (qPCR). Additionally, evaluation of two types of collection media (PBS and TF transport tube) were conducted that evaluated sample stability from 0-3 days when stored at 4 °C or 25 °C. Extended incubation times for PBS media were also evaluated (5, 7 and 14 days) at both refrigeration and frozen temperatures to evaluate the effect of extended transport time on samples. Limits of detection (LOD), dynamic range, and RNA stability were assessed using lab cultured TF spiked into samples of normal bovine smegma collected in PBS or TF transport media and performance was assessed on field samples collected in parallel. Direct RT-qPCR was found to be equivalent or superior to qPCR, with 100% agreement at 10 parasites/extraction and a LOD of 1 parasite/extraction. PBS was not significantly different from TF transport media for TF RNA stability when incubated at both temperatures up to 3 days of incubation. Additionally, the extended incubation experiments indicate that samples containing 10 parasites/extraction can be detected when held at 4 °C for 5 days with a mean Cq 26.34 (95% CI: 23.11 - 29.58) and detected when held at -20 °C for 7 or 14 days, with a mean Cq 29.55 (95% CI: 27.73 - 31.37). A significant decrease in detectable RNA was observed at samples containing less than 10 parasites/extraction when held at -20 °C for 14 days, which should be considered for long term storage. The findings of the current study demonstrate the utility of PBS collection media in conjunction with the direct RT-qPCR which allows for more flexibility during sample collection and transport and ultimately enhancement of TF surveillance programs.